2005
DOI: 10.1523/jneurosci.3842-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Disintegration of the Sleep-Wake Cycle and Circadian Timing in Huntington's Disease

Abstract: Sleepdisturbancesinneurologicaldisordershaveadevastatingimpactonpatientandcareralike.However,theirpathologicaloriginisunknown.Here we show that patients with Huntington's disease (HD) have disrupted night-day activity patterns. This disruption was mirrored in a transgenic model of HD (R6/2 mice) in which daytime activity increased and nocturnal activity fell, eventually leading to the complete disintegration of circadian behavior. The behavioral disturbance was accompanied by marked disruption of expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
311
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(336 citation statements)
references
References 40 publications
22
311
2
1
Order By: Relevance
“…As stated above (Section 1), there is a disintegration of the normal sleep-wake cycle and circadian rhythms in R6/2 mice (Morton et al, 2005b), and this deregulation can contribute, at least in part, to the cognitive deficits observed in these transgenic mice. Thus, in a recent study R6/2 mice were treated with the sedative drug chloral hydrate or alprazolam (a short-acting benzodiazepine) to test whether circadian and cognitive disturbances could be reversed by imposing a daily cycle of sleep .…”
Section: Alternative Pharmacological Therapeutic Strategiesmentioning
confidence: 85%
See 1 more Smart Citation
“…As stated above (Section 1), there is a disintegration of the normal sleep-wake cycle and circadian rhythms in R6/2 mice (Morton et al, 2005b), and this deregulation can contribute, at least in part, to the cognitive deficits observed in these transgenic mice. Thus, in a recent study R6/2 mice were treated with the sedative drug chloral hydrate or alprazolam (a short-acting benzodiazepine) to test whether circadian and cognitive disturbances could be reversed by imposing a daily cycle of sleep .…”
Section: Alternative Pharmacological Therapeutic Strategiesmentioning
confidence: 85%
“…On the other hand, "dark cell degeneration" has also been described in a small number of neurons in 12- (Stack et al, 2005) and 14-week-old mice (i.e., at a very late stage in the development of the disease) (Iannicola et al, 2000;Turmaine et al, 2000;Yu et al, 2003). Moreover, a progressive loss of orexin neurons was found in the lateral hypothalamus of R6/2 mice, which was correlated with the occurrence of narcoleptic-like episodes and seemed to be related with a disintegration of the sleep-wake cycle and of the circadian rhythm in these mice (Morton et al, 2005b). Furthermore, a loss of retinal ganglion neurons was reported in these transgenic animals (Helmlinger et al, 2002).…”
Section: Introduction -The R6 Micementioning
confidence: 93%
“…Consistence with our hypothesis, attenuated expression of mBmal1 in SCN was reported to accompany disrupted rest-activity patterns in mouse models. 88 Furthermore, the CLOCK mutant mice, which have reduced pacemaker amplitude, 89 showed mania-like behavior. 90 It has been reported that reduced amplitude of circadian oscillators can increase the efficacy of perturbing agents such as light and other stimuli in causing phase shifts in various organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with either Parkinson's or Alzheimer's disease, the number of cells does not change, but their characteristics do: they undergo cytoskeletal alterations and manifest cytoplasmatic inclusions such as Levy bodies (Hofman, 1997;Braak and Braak, 1998;Kremer, 1992;Kremer et al, 1990;Kremer and Bots, 1993). The fact that patients with neurodegenerative disease often suffer from cachexia and sleep disorders during the later stages of their disease (Kremer, 1992;Braak and Braak, 1992;Morton et al, 2005), supports the contention that the human LTN may be involved in the regulation of food intake and of the sleep-wake cycle.…”
Section: Discussionmentioning
confidence: 99%